Long-term administration of bumetanide improve functional recovery after spinal cord injury in rats - Hashemizadeh, Shiva; Gharaylou, Zeinab; Hosseindoost, Saereh; Sardari, Maryam; Omidi, Ameneh; Hosseini ravandi, Hassan; Hadjighassem, Mahmoudreza (Frontiers in Pharmacology, 2022)
Ion disturbances are among the most remarkable deficits in spinal cord injury (SCI). GABA is an integral part of the neural interaction. Action of GABAA receptor depends on the amount of intracellular chloride. Homeostasis of chloride is controlled by two co-transporters, NKCC1 and KCC2. Previous studies revealed that NKCC1 are disturbed in SCI. In this study, NKCC1 is highly expressed in the epicenter of lesioned spinal cord at three hours after induction of lesion and reached to the peak around six hours after SCI. Bumetanide (2 and 4 mg/day), as a specific NKCC1 inhibitor, was used at three hours post-SCI for 28 days. The functional recovery outcomes were measured by the Basso Beattie Bresnahan (BBB) locomotor rating scale, the ladder walking test, and the hot plate test. The rats that received bumetanide 4 mg/day exhibited improved recovery of locomotor function, reduction of NKCC1 gene expression, and upregulation of GAP protein levels 28 days post-SCI. Histological tissue evaluations confirmed bumetanide's neuroprotective and regenerative effect. This study provides novel evidence for the benefits of bumetanide in early administration after SCI.